Ceftazidime-Avibactam for the Treatment of Multidrug-Resistant Pathogens: A Retrospective, Single Center Study - Maria Di Pietrantonio; Lucia Brescini; Jennifer Candi; Morroni Gianluca; Francesco Pallotta; Sara Mazzanti; Paolo Mantini; Bianca Candelaresi; Silvia Olivieri; Francesco Ginevri; Giulia Cesaretti; Sefora Castelletti; et al. (MDPI AG, 2022)
Background: Ceftazidime/avibactam is a new cephalosporin/beta-lactamase inhibitor combination approved in 2015 by the FDA for the treatment of complicated intra-abdominal and urinary tract infection, hospital-acquired pneumoniae and Gram-negative infections with limited treatment options. Methods: In this retrospective study, we evaluate the efficacy of ceftazidime/avibactam treatment in 81 patients with Gram-negative infection treated in our center from January 2018 to December 2019. The outcome evaluated was 30-days survival or relapse of infection after the first positive blood culture. Results: the majority of patients were 56 male (69%), with median age of 67. Charlson's Comorbidity Index was >3 in 58 patients. In total, 46% of the patients were admitted into the medical unit, 41% in the ICU, and 14% in the surgical ward. Of the patients, 78% had nosocomial infections, and 22% had healthcare-related infections. The clinical failure rate was 35%: 13 patients died within 30 days from the onset of infection. The outcome was influenced by the clinical condition of the patients: solid organ transplantation (p = 0.003) emerged as an independent predictor of mortality; non-survival patients most frequently had pneumonia (p = 0.009) or mechanical ventilation (p = 0.049). Conclusion: Ceftazidime-avibactam showed high efficacy in infections caused by MDR Gram-negative pathogens with limited therapeutic options.